Evaluation of optical density of bone defects filled with calcium phosphate cement and bioactive glass in rats - Biancon Filho,Luiz Alberto (2011)
Purpose: To evaluate new bone formation, by the analysis of optical density, in rat femoral defects filled with calcium phosphate cement (CPC) and bioactive glass (BG). Methods: Twenty-one rats were divided into three groups, Group I (CPC), Group II (BG), and Group III (control), and assessed after 7, 15, and 30 days. Three bone cavities were made in the left femur and filled with CPC, BG, and no material (control). Digital images were obtained and the results were subjected to statistical analysis of variance (ANOVA), complemented by the Friedman and Kruskal-Wallis nonparametric tests, with a significance level of 5%. Results: Regarding optical density, Group I showed statistical values significantly higher than Group III and also higher, although not statistically significant, than Group II, in all observation periods. When Groups II and III were compared, Group II showed higher optical density values, without statistically significant differences, in all periods. Conclusion: The biomaterials analyzed showed higher optical density in relation to the control group in all observation periods, calcium phosphate cement being the best option in the repair of bone defects, but without statistically significant differences in relation to bioactive glass.